Die Bildersprache der Johannesapokalypse: Ferdinand Hahn zum 75. Geburtstag - Frey, Jörg (Zeitschrift für Theologie und Kirche, 2001)
Revelation is a 'picture book.' This explains its enormous influence in the field of art, but also explains how difficult it is to interpret. In this article, the author discusses several approaches to the language of imagery, the origin of the images, their literary structure and their connection to one another as well as the specific rhetorical impact of the sequence of images in Revelation.